COLD, POOR AND FRAIL: A CROSS-SECTIONAL STUDY WITH COMMUNITY DWELLING OLDER PEOPLE IN JAPAN. (11th November 2018) - Nakajima, Y; M Schmidt, S; Malmgren Fänge, A; Hoshi, T; Ono, M; Ikaga, T
Abstract: This study investigated the relationship between perceived indoor temperature in winter and risk for frailty. This was a cross-sectional study and included 264 community dwelling older adults living in Japan. Participants completed self-reported questions about personal characteristics, frailty, housing, and perceived indoor temperature in winter. Participants were grouped based on perceived temperature (Cold or Warm) and economic satisfaction (Unsatisfied or Satisfied). ANCOVA and MANCOVA were used to examine group differences in frailty. An interaction effect showed that people in the Cold group and unsatisfied economically scored significantly worse on the frailty index (F(1, 252)=7.61, p=0.006). Risk for falls was the major contributor to poorer scores on the frailty index among those in the Cold group and unsatisfied economically (F(1, 252)=13.91, p<.001). These finding suggest that policies that support older adults to maintain a warm home in the winter could help to prevent frailty.